2022
DOI: 10.1186/s12879-022-07933-y
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of acute liver failure with intrahepatic cholestasis due to dengue hemorrhagic fever: CytoSorb® and plasma exchange aided in the recovery: case report

Abstract: Background Dengue haemorrhagic fever is a severe form of acute dengue infection characterized by leakage of plasma through capillaries into body spaces resulting in circulatory insufficiency leading to shock. Despite varying degrees of liver involvement occurring in acute dengue infection, intrahepatic cholestasis is very rare in the literature with only two cases reported so far. We report a challenging case of a middle-aged woman with DHF complicated by acute liver failure, coagulopathy, acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although no specific treatment is recommended, there is increasing interest in using intravenous N-acetylcysteine (NAC) for managing such cases. Even in our cohort, 6 (31.6%) patients were administered NAC for ALF, albeit in different doses and wide variation of duration[ 12 , 15 , 16 , 17 , 20 , 30 ]. NAC is the recommended antidote for managing ALF secondary to paracetamol overdose[ 40 ], but is increasingly been used in managing non-paracetamol related ALF[ 41 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although no specific treatment is recommended, there is increasing interest in using intravenous N-acetylcysteine (NAC) for managing such cases. Even in our cohort, 6 (31.6%) patients were administered NAC for ALF, albeit in different doses and wide variation of duration[ 12 , 15 , 16 , 17 , 20 , 30 ]. NAC is the recommended antidote for managing ALF secondary to paracetamol overdose[ 40 ], but is increasingly been used in managing non-paracetamol related ALF[ 41 ].…”
Section: Discussionmentioning
confidence: 94%
“…Therapies like cytokine filtration, plasma exchange and molecular adsorbent recirculating system have also been used in patients with severe ALF. However, large scale data is missing to recommend their routine use[ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,20,25,27,30,31,36,40,47,61,75,110,112,118,125,130,133,143,[149][150][151] Transaminase elevation was detected between symptom onset and day 8. 41,48,51,54,55,80,140,141,145,147,152,153 Longitudinal sampling of dengue patients showed that the rise in transaminases had often already started at the first sampling time point, usually between day 1 and 5 from disease onset. 16,24,41,48,54,57,59,152,154,155 Transaminase levels increased during hospitalisation, 47 and from week 1 to 2 postsymptom onset, 47 usually peaking between day 1 and 11 postsymptom onset 16,24,27,42,52,54-57,59,67,68,74,85,91,94,104,135,139,141,144,152, 154-156 and occasionally during the convalescent phase.…”
Section: Nausea/ Vomitingmentioning
confidence: 99%
“…5 Severe dengue, independently capable of precipitating acute liver failure through direct hepatotoxicity, likely presents a significant compounding risk in patients receiving ATT. 6 Case reports 7,8 suggest complex interactions between dengue and hepatotoxic medications, potentially involving reduced clearance, aberrant hapten formation, and synergistic immunotargeting. 9 While isolated dengueinduced liver injury often resolves spontaneously, concomitant drug-induced acute liver failure carries a grave prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports 7,8 suggest complex interactions between dengue and hepatotoxic medications, potentially involving reduced clearance, aberrant hapten formation, and synergistic immunotargeting 9 . While isolated dengue‐induced liver injury often resolves spontaneously, concomitant drug‐induced acute liver failure carries a grave prognosis 10 .…”
Section: Introductionmentioning
confidence: 99%